Reconstruction of Management Cost Allocation During the Transitional Period of Apartment Housing Based on Justice and Legal Certainty - Saputro, Denny Wibisono (Dinasti Research, 2025)
The development of apartment housing in Indonesia represents a strategic initiative to provide decent housing amid the scarcity of urban land. However, regulations governing the transitional period before the establishment of the Association of Owners and Occupants of Apartment Units (PPPSRS) remain inconsistent, leading to legal uncertainty and injustice, particularly in the allocation of management costs. This study aims to analyse weaknesses in existing regulations, evaluate their implementation in practice, and propose a legal reconstruction that guarantees fairness and legal certainty for both developers and occupants. The research employs a normative and empirical juridical approach through the analysis of laws, court decisions, case studies, and comparative studies with practices in other countries. The findings reveal that Government Regulation No. 13 of 2021, which fails to recognize the Sale and Purchase Binding Agreement (PPJB) as valid interim ownership evidence, imposes a disproportionate financial burden on developers. The proposed legal reconstruction includes recognizing fully paid PPJB as a temporary proof of ownership, implementing proportional cost-sharing based on the Proportional Comparison Value (NPP), and strengthening government oversight during the transitional period. In conclusion, a new regulatory framework is required to establish an apartment management system that is fair, transparent, and legally certain, in accordance with the principles of a responsive rule of law.